KONSISTENSI PERENCANAAN PENGANGGARAN DAN PELAKSANAAN APBDes DESA BUKIT SEMBILAN KECAMATAN BANGKINANG KABUPATEN KAMPAR - Lukita Uli Hotma; Putro Sukirno Tri; Taryono Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to find out how the APBDes planning, APBDes budgeting, APBDes implementation and the consistency of planning, budgeting and implementing APBDes, the object of this research is the village of Bukit Sembilan, Bangkinang District, Kampar Regency. The analytical method used in this study is a qualitative descriptive method with an explanation of the data in the form of numbers. The data collection technique in this research is through the study of various reports, namely by collecting data from various literatures related to the problems studied. The results of the analysis show that in the village APBDes planning variables in the RPJMDes and RKPDes documents there are differences in the types of activities and budgets. Whereas in the APBDes budgeting variable, the largest income received by the village comes from the Village Fund (DD) and the largest village expenditure is on the implementation of development. Furthermore, the APBDes implementation variable is where in the implementation of the types of activities there are types of activities that cannot be carried out because these types of activities are considered not to be a priority for village needs and the budget is not available to carry out these types of activities. Then on the variables of consistency of planning, budgeting and implementation of APBDes in Bukit Sembilan village, it is found that the consistency of APBDes planning is inconsistent where the results of the comparison of RPJMDes with RKPDes are more than 100%, then the consistency of APBDes budgeting is inconsistent where the comparison of RKPDes with APBDes is less than 100%, and consistency the implementation of APBDes, namely inconsistencies where the comparison of implementation with APBDes is more than 100%Keywords: RPJMDes, RKPDes, APBDes, Implemetation